2007
DOI: 10.1002/hbm.20505
|View full text |Cite
|
Sign up to set email alerts
|

Model‐free group analysis shows altered BOLD FMRI networks in dementia

Abstract: FMRI research in Alzheimer's disease (AD) and mild cognitive impairment (MCI) typically is aimed at determining regional changes in brain function, most commonly by creating a model of the expected BOLD-response and estimating its magnitude using a general linear model (GLM) analysis. This crucially depends on the suitability of the temporal assumptions of the model and on assumptions about normality of group distributions. Exploratory data analysis techniques such as independent component analysis (ICA) do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
97
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 46 publications
(49 reference statements)
12
97
0
1
Order By: Relevance
“…The main result of this study is that APOE‐ε4 carriers show decreased EC in comparison with noncarriers in visual cortical regions; which have previously been demonstrated to be affected in MCI and AD (Rombouts et al., 2009; Sanz‐Arigita et al., 2010). Furthermore, lower EC values were associated with older age and worse visual task performance in noncarriers.…”
Section: Discussionmentioning
confidence: 99%
“…The main result of this study is that APOE‐ε4 carriers show decreased EC in comparison with noncarriers in visual cortical regions; which have previously been demonstrated to be affected in MCI and AD (Rombouts et al., 2009; Sanz‐Arigita et al., 2010). Furthermore, lower EC values were associated with older age and worse visual task performance in noncarriers.…”
Section: Discussionmentioning
confidence: 99%
“…In AD, deficits in a cognitive domain are typically linked to metabolic and structural abnormalities in the corresponding brain regions, and the pattern of these abnormalities in AD predicts the manifestation of cognitive loss in this disease. For example, hippocampal atrophy and functional changes is associated with deterioration in memory in AD (Desgranges et al 1998;Desgranges et al 2002;Chetelat et al 2003;Gilboa et al 2005;Celone et al 2006;Rombouts et al 2009;, while metabolic decline of the parietal cortex and posterior cingulate is evident at the earliest stages of the disease as well as associated with visual-spatial A c c e p t e d M a n u s c r i p t impairments (Duara et al 1986;Meguro et al 2001;Alexander et al 2002;Drzezga et al 2003;Ishii et al 2005). However, this association of cognitive deficits with regional brain pathology is limited because cognitive functions are usually not underpinned by a single cortical region but by a network of regions forming so called 'degenerate systems' which can fully or partially sustain the cognitive function even when one region or part of the network has been damaged (Noppeney et al 2004).…”
Section: Network Architecture Of the Brainmentioning
confidence: 99%
“…Recent R-fMRI studies have identified putative biomarkers of neuropsychiatric illness (12,(15)(16)(17)(18), provided insight into the development of functional networks in the maturing and aging brain (19)(20)(21)(22), demonstrated a shared intrinsic functional architecture (23) between humans and nonhuman primates (24,25), and delineated the effects of sleep (26), anesthesia (27), and pharmacologic agents on R-fMRI measures (28,29). Given the many sources of variability inherent in fMRI, the remaining challenge is to demonstrate the feasibility and utility of adopting a high-throughput model for RfMRI, commensurate with the scale used by human genetics studies to have the power to detect both single gene and combinatorial genetic and environmental effects on complex phenotypes.…”
mentioning
confidence: 99%